(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the classification of the peculiarities and possibilities of experimental phonetics in linguistics. It also provides information about the definitions of experimental phonetics, its history, objectives and practical and theoretical research carried out in this field around the world.